Green Space Cooling Effect and Contribution to Mitigate Heat Island Effect of Surrounding Communities in Beijing Metropolitan Area - Liu, Wei; Zhao, Haiyue; Sun, Shibo; Xu, Xiyan; Huang, Tingting; Zhu, Jianning (Frontiers in Public Health, 2022)
With the rapid process of urbanization and global warming, many metropolises are vulnerable to high temperature in summer, threatening the health of residents. However, greenspaces can generate cooling effect to mitigate the urban heat island effect in big cities. They can also help to improve the living quality and well-being of surrounding residents. In this paper, we utilized radiative transfer equation algorithm, k-means clustering algorithm, big data crawling and spatial analysis to quantify and map the spatial distribution, cooling capacity and cooling contribution for community of 1157 greenspaces within Beijing Fifth Ring Road, a typical metropolitan area. The findings showed that: (1) the area proportion of heat island in the study area is larger than that of cooling island. Accounting for only about 30% area in the study area, the greenspaces reduce the average land surface temperature by 1.32℃. (2) the spatial features of greenspace, such as area and shape complexity, had a significant influence on its cooling effect. (3) 4 clusters greenspaces with specific spatial features and cooling capacity were identified. And there were differences among these clusters in greenspace cooling contribution for surrounding communities. (4) the differences of greenspace cooling contribution also existed in different urban zones. In specific, the middle zone performed significantly better than that in the inner and outer zones. (5) we furthered in finding that some greenspaces with medium and high cooling contribution need to improve their cooling capacity soon, and some greenspaces with low cooling contribution or no contribution have good potential for constructing new communities in the future. Our study could help planners and government understand the current cooling condition of greenspaces, so as to improve their cooling capacity, mitigate the urban heat island effect and create a comfortable and healthy thermal environment in summer.